2021
DOI: 10.1007/s00134-021-06451-w
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of new ECMO centers during the COVID-19 pandemic: experience and results from the Middle East and India

Abstract: Purpose Extracorporeal membrane oxygenation (ECMO) use for severe coronavirus disease 2019 (COVID-19) patients has increased during the course of the pandemic. As uncertainty existed regarding patient’s outcomes, early guidelines recommended against establishing new ECMO centers. We aimed to explore the epidemiology and outcomes of ECMO for COVID-19 related cardiopulmonary failure in five countries in the Middle East and India and to evaluate the results of ECMO in 5 new centers. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 38 publications
1
55
0
Order By: Relevance
“…In the earliest phases of the pandemic, the use of extracorporeal life support in patients with severe coronavirus disease 2019 (COVID-19) was associated with disastrous outcomes. However, later series have shown better results, with hospital mortality ranging from 30 to 60% [ 1 3 ]. These series included patients receiving support during the first wave of the pandemic.…”
mentioning
confidence: 99%
“…In the earliest phases of the pandemic, the use of extracorporeal life support in patients with severe coronavirus disease 2019 (COVID-19) was associated with disastrous outcomes. However, later series have shown better results, with hospital mortality ranging from 30 to 60% [ 1 3 ]. These series included patients receiving support during the first wave of the pandemic.…”
mentioning
confidence: 99%
“…In patients with respiratory failure from SARS-CoV-2 infection who required the use of ECMO, the mortality rate varied considerably between studies ranging from 31 to > 80% [ 25 29 ]. We report a higher mortality rate (48.9%) in severe SARS-CoV-2 patients treated with ECMO due to ARDS; compared to the rates reported by three studies in Paris, France (31%) [ 25 ], Michigan, USA (< 40%) [ 26 ], and an international study conducted in the Middle East and India (41.7%) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with respiratory failure from SARS-CoV-2 infection who required the use of ECMO, the mortality rate varied considerably between studies ranging from 31 to > 80% [ 25 29 ]. We report a higher mortality rate (48.9%) in severe SARS-CoV-2 patients treated with ECMO due to ARDS; compared to the rates reported by three studies in Paris, France (31%) [ 25 ], Michigan, USA (< 40%) [ 26 ], and an international study conducted in the Middle East and India (41.7%) [ 29 ]. Nevertheless, we report a very similar and slightly lower survival rate (51.1%) compared to the previous study done in the USA (53.8%) [ 30 ], which was compatible to the data from the European branch of the Extracorporeal Life Support Organization international survey [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial recommendations suggested that starting up a new ECMO center during the pandemic was not advisable [ 23 ]. One study that challenged this notion was a retrospective, multicenter, observational study of 307 patients who received ECMO for COVID-19 from 19 ECMO centers across five countries in the Middle East and India [ 32 ]. Whereas overall survival was 45%, survival at new ECMO centers was 55%, exceeding the 41% survival at established ECMO centers [odds ratio (OR) 1.65; 95% CI 0.75–3.67], albeit with a wide confidence interval and the almost certain presence of residual confounding including in patient selection [ 32 ].…”
Section: Extracorporeal Membrane Oxygenation Resource Constraints and Crisis Standards Of Carementioning
confidence: 99%